Klebsiella pneumoniae exhibiting a phenotypic hyper-splitting phenomenon including the formation of small colony variants - Doğan, Eyüp; Sydow, Katharina; Heiden, Stefan E.; Eger, Elias; Wassilew, Georgi; Proctor, Richard A.; Bohnert, Jürgen A.; Idelevich, Evgeny A.; Schaufler, Katharina; Becker, Karsten (Frontiers in Cellular and Infection Microbiology, 2024)
In this study, we characterized a Klebsiella pneumoniae strain in a patient with shrapnel hip injury, which resulted in multiple phenotypic changes, including the formation of a small colony variant (SCV) phenotype. Although already described since the 1960s, there is little knowledge about SCV phenotypes in Enterobacteriaceae. The formation of SCVs has been recognized as a bacterial strategy to evade host immune responses and compromise the efficacy of antimicrobial therapies, leading to persistent and recurrent courses of infections. In this case, 14 isolates with different resisto-and morpho-types were distinguished from the patient's urine and tissue samples. Whole genome sequencing revealed that all isolates were clonally identical belonging to the K. pneumoniae high-risk sequence type 147. Subculturing the SCV colonies consistently resulted in the reappearance of the initial SCV phenotype and three stable normal-sized phenotypes with distinct morphological characteristics. Additionally, an increase in resistance was observed over time in isolates that shared the same colony appearance. Our findings highlight the complexity of bacterial behavior by revealing a case of phenotypic "hyper-splitting" in a K. pneumoniae SCV and its potential clinical significance.